Model Pengembangan Sistem Akutansi Sebagai Kelola Informasi Akuntansi Pada Taman Pendidikan Al-Qur’an (TPQ) Nurul Huda Sukun Malang - Alifianto, Muhammad Budi; Nurbatin, Defia (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
The purpose of this research is to produce an Accounting System model in the form of Standard Operating Procedure (SOP) as a guide to the accuracy of Accounting Information at TPQ Nurul Huda Malang. This type of research is a modified research and development model from Fitriana (2016). The research phase starts from problem identification, data collection, product preparation, product testing (expert validation) and final product refinement. Data collection techniques are Focus Group Discussion, Observation, Interview and questionnaire (questionnaire). The questionnaire as an expert validation instrument consists of 4 aspects of assessment, namely aspects of usability, convenience, completeness and readability. The technique used to analyze the data from the validation scoring results is to use the average test value. This study resulted in a quality system in the form of 10 SOP for Financial Recording Information Flow and 8 SOP for Financial Management Information Flows which showed that the implementation of SOP had value feasibility to be implemented and in accordance with user needs.